Pre-Service Teachers’ Perceptions of Kahoot! as a Teaching Tool During Internships - Tiara Maharani; Siswana (SALEE: Study of Applied Linguistics and English Education, 2025)
This study explores how pre-service teachers perceive the use of Kahoot! during their teaching internships, especially in English language classrooms. As digital tools become more common in education, Kahoot! stands out for making lessons more interactive and enjoyable. Through a survey of 180 education students, this research looks at how Kahoot! supports engagement, ease of use, and effectiveness in teaching. Most participants found it helpful in boosting student motivation and participation. They also saw it as simple to use and easy to apply in the classroom. Interestingly, factors like a student's semester and age influenced how effective they thought Kahoot! was, while their study program and how often they used it did not. Overall, the study shows that gamified tools like Kahoot! can enhance the teaching experience and suggests that teacher education programs should consider including them to make learning more dynamic and effective.